PENGARUH APLIKASI MODEL PEMBELAJARAN TPS, NHT, DAN KONVENSIONAL TERHADAP KETERAMPILAN SOSIAL SISWA - Hepy Novadila; Pargito Pargito; Yon Rizal (Faculty of Teacher Training and Education, University of Lampung, 2014)
The objective of this research is to know: the difference of students social skills average in Think Pair Square learning model, numbered head together learning model, and conventional learning model. This research uses quasi experiment method by descriptive and quantitative approached. The design of quasi eksperiment uses post test only non equivalent control group design. The results of this research show that: (1) there are the difference of students social skills average in Think Pair Square learning model, numbered head together learning model, and conventional learning model, (2) The students social skills average in Think Pair Square learning model is better than numbered head together learning model, (3) The students social skills average in Think Pair Square learning model is better than conventional learning model, (4) The students social skills average in numbered head together learning model is better than conventional learning model.Penelitian ini bertujuan untuk mengetahui: perbedaan rata-rata keterampilan sosial pada model pembelajaran Think Pair Square, model pembelajaran Numbered Head Together, dan model pembelajaran konvensional. Metode penelitian menggunakan Quasi Eksperimen secara deskriptif dan kuantitatif dengan desain penelitian Post Test Only, Non Equivalent Control Group Design. Hasil penelitian menunjukkan bahwa: (1) Terdapat perbedaan rata-rata keterampilan sosial siswa pada model pembelajaran Think Pair Square, model pembelajaran Numbered Head Together, dan model pembelajaran konvensional, (2) Rata-rata Keterampilan Sosial Siswa pada Model Pembelajaran Think Pair Square lebih baik dibandingkan model pembelajaran Numbered Head Together, (3) Rata-rata keterampilan sosial siswa pada model pembelajaran Think Pair Square lebih baik dibandingkan model pembelajaran konvensional, (4) Rata-rata keterampilan sosial siswa pada model pembelajaran Numbered Head Together lebih baik dibandingkan model pembelajaran konvensional.Kata kunci: keterampilan sosial, numbered head together, pembelajaran konvensional, think pair square